Functional characterization of an arrestin gene on insecticide resistance of Culex pipiens pallens - Sun Yan; Zou Ping; Yu Xin-You; Chen Chen; Yu Jing; Shi Lin-Na; Hong Shan-Chao; Zhou Dan; Chang Xue-Lian; Wang Wei-Jie; Shen Bo; Zhang Dong-Hui; et al. (Parasites & Vectors, 2012)
Abstract Background Continuous and excessive application of insecticides has resulted in the rapid development of insecticide resistance in several mosquito species, including Culex pipiens pallens. Previous studies in our laboratory found that arrestin gene expression was higher in the deltamethrin-resistant (DR) strain than in the deltamethrin-susceptible (DS) strain of Cx. pipiens pallens. Similarly, other studies reported that arrestin was highly expressed in permethrin-resistant Cx. quinquefasciatus and in dichlorodiphenyltrichloroethane (DDT)-resistant Drosophila melanogaster. Methods Full-length cDNAs of an arrestin gene were cloned from Cx. pipiens pallens via polymerase chain reaction (PCR) and rapid amplification of cDNA end (RACE). The mRNA levels of the arrestin gene in the whole life cycle of DR and DS strains of Cx. pipiens pallens were investigated via quantitative real-time PCR. In addition, the relationship between arrestin and deltamethrin (DM) resistance were identified using genetic overexpression strategies and arrestin RNAi in mosquito cells. Cell viability was analyzed with cholecystokinin octapeptide after DM treatment. Moreover, the mRNA levels of cytochrome P450 6A1 (CYP6A1) and opsin in the transfected cells and controls were analyzed. Results Complete arrestin gene sequence was cloned and expressed throughout the life cycle of Cx. pipiens pallens. Moreover, arrestin was significantly upregulated in the DR strain, compared with that in the DS strain at the egg, pupae, and adult stages. Arrestin overexpression comparably increased the mosquito cell viability, whereas arrestin knockdown by siRNA decreased mosquito cell viability with deltamethrin (DM) treatment. Meanwhile, the mRNA levels of CYP6A1 and opsin were upregulated in mosquito cells transfected with arrestin and downregulated in mosquito cells with arrestin knockdown. Conclusion This study presented the first evidence that arrestin might be associated with insecticide resistance in Cx. pipiens pallens.